Effectiveness of Steroid Therapy on Pneumonic Chronic Obstructive Pulmonary Disease Exacerbation: A Multicenter, Retrospective Cohort Study - Shiroshita A (International Journal of COPD, 2020)
Akihiro Shiroshita,1,2 Hiroshi Shiba,3 Yu Tanaka,4 Akihiro Nishi,5 Kenya Sato,6 Chigusa Shirakawa,7 Yuki Kataoka7,8 1Department of Respiratory Medicine, Ichinomiyanishi Hospital, Ichinomiya, Japan; 2Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USA; 3Post Graduate Education Center, Kameda Medical Center, Kamogawa, Japan; 4Department of Pulmonology, Kameda Medical Center, Kamogawa, Japan; 5General Medicine, Awa Regional Medical Center, Tateyama, Japan; 6Department of Thoracic Medicine, Saiseikai Yokohamashi Tobu Hospital, Yokohama, Japan; 7Department of Respiratory Medicine, Hyogo Prefectural Amagasaki General Medical Center, Amagasaki, Japan; 8Hospital Care Research Unit, Hyogo Prefectural Amagasaki General Medical Center, Amagasaki, JapanCorrespondence: Akihiro ShiroshitaDepartment of Respiratory Medicine, Ichinomiyanishi Hospital, 1 Kaimeihira, Ichinomiya, Aichi 494-0001, JapanTel +81-80-3807-4960Fax +586-48-0077Email akihirokun8@gmail.comPurpose: To date, no consensus exists on the effects of systemic steroid use on pneumonic chronic obstructive pulmonary disease (COPD) exacerbation owing to trial design issues in previous trials involving these conditions. This multicenter study aimed to evaluate more precisely the effectiveness of the use of systemic steroids in treating pneumonic COPD exacerbation in a larger sample by adjusting for confounding factors.Patients and Methods: This multicenter, retrospective, observational study was conducted across five acute general hospitals in Japan. We analyzed the association between parenteral/oral steroid therapy and time to clinical stability in pneumonic COPD exacerbation. We used a validated algorithm derived from the 10th revision of the International Classification of Diseases and Related Health Problems (ICD-10) to include patients with pneumonic COPD exacerbation. We excluded patients with other hypoxia causes (asthma exacerbation, pneumothorax, heart failure) and complicated pneumonia (obstructive pneumonia, empyema), those who required tracheal intubation/vasopressors, and those who were clinically stable on day of admission. The primary outcome was the time to clinical stability. Multiple imputation was used for missing data. Propensity scores within each imputed dataset were calculated using potential confounding factors. The Fine and Gray model was used within each dataset to account for the competing risk of death and hospital discharge without clinical stability, and we combined the results.Results: Altogether, 1237 patients were included. Systemic steroid therapy was administered to 658 patients (53%). The pooled estimated subdistribution hazard ratio of time to clinical stability in steroid vs non-steroid users was 0.89 (95% confidence interval, 0.78 to 1.0).Conclusion: This study revealed that systemic steroid therapy may not improve the time to clinical stability in patients with pneumonic COPD exacerbation of mild to moderate severity. Further randomized controlled trials including more severe patients will be needed to evaluate the effectiveness of systemic steroid therapy accurately.Keywords: COPD, pneumonia, steroid, outcomes, mortality